Risk factors for injury in child and adolescent sport: A systematic review of the literature - Emery, C. A. (Clinical Journal of Sport Medicine, 2003)
Objective: The objective of this systematic review of the literature is to identify risk factors and potential prevention strategies that may modify risk factors for injury in child and adolescent sport. Data Sources: Seven electronic databases were searched to identify potentially relevant articles. A combination of Medical Subject Headings and text words were used (athletic injuries, sports injury, risk factors, adolescent, and child). Study Selection: This review is based on epidemiological evidence in which the data are original, an exposure and outcome are objectively measured, and an attempt is made to create a comparison group. Forty-five studies were selected for this review. Data Extraction: The data summarized include study design, study population, exposures, outcomes, and results. Estimates of odds ratios or relative risks were calculated where study data were adequate to do so. The quality of evidence is based on internal validity, external validity, and causal association. Data Synthesis: There is some evidence that potentially modifiable risk factors including poor endurance, lack of preseason training, and some psychosocial factors are important risk factors for injury in child and adolescent sport. Concerns with study design, internal validity, and generalizability persist. The evidence is consistent, however, with more convincing evidence from adult population studies. The evidence for nonmodifiable risk factors for injury in adolescent sport (ie, age, sex, previous injury) is consistent among studies. Conclusions: Sport participation and injury rates in child and adolescent sport are high. This review will assist in targeting the relevant groups and designing future research examining risk factors and prevention strategies in child and adolescent sport. Future clinical trials addressing modifiable risk factors to reduce the incidence of sports injury in this population are necessary.